How Technology Affects Our Social Life - Elle Syuhailah (IC-ITECHS, 2020)
Social life can be seen as one of the most important aspects in our lives. Research has shown that a good social life results in good mental and physical health because social interactions can lower the risk of Dementia. Although our social interaction is entirely disrupted due to the pandemic of Covid-19, it is very crucial to maintain a good social life because our social life has been dramatically altered through technological advances. Due to the virus, we cannot physically see each other that resulted in a prolonged exposure to stress. So, it is clear that people would find another alternative to interact with their family and friends and social media is the solution as a medium of social interaction. It has brought us closer together as a community by increasing our communication with each other and reducing the gap between us. As a result of its simplicity and the basic sources of comfort followed by entertainment that it provides, technology can be said to be rather addictive. It is necessary to strike a balance between real life and cyberspace as well as it is crucial to instill awareness amongst Internet users especially youngsters about Internet Etiquette. The particular reason for this circumstance is social media has also been associated with an increased incidence of complaints regarding mental health. Research has shown that Internet addiction is becoming a widespread problem, particularly among younger populations. Although not all young people's mental health problems can be related to technology, it is important to consider the large majority of children plagued by these issues. The study finds that before they reach maturity, 1 in every 5 children between the ages of 13-18 have, or may have, a severe mental disorder.